Values of the apparent diffusion coefficient in the differential diagnosis of tumors of the posterior fossa in the pediatric population of Colombia - Andrés Fernando López-Cadena; Luz Ángela Moreno-Gómez; Diego Armando Guerrero-Gómez (Revista de la Facultad de Medicina)
Introduction: Posterior fossa tumors are common in the pediatric population and require adequate characterization by means of structural magnetic resonance imaging (MRI) and advanced MRI techniques to achieve an appropriate therapeutic approach.